If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12.3 + 4x = 2x + -9.2 Reorder the terms: 12.3 + 4x = -9.2 + 2x Solving 12.3 + 4x = -9.2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12.3 + 4x + -2x = -9.2 + 2x + -2x Combine like terms: 4x + -2x = 2x 12.3 + 2x = -9.2 + 2x + -2x Combine like terms: 2x + -2x = 0 12.3 + 2x = -9.2 + 0 12.3 + 2x = -9.2 Add '-12.3' to each side of the equation. 12.3 + -12.3 + 2x = -9.2 + -12.3 Combine like terms: 12.3 + -12.3 = 0.0 0.0 + 2x = -9.2 + -12.3 2x = -9.2 + -12.3 Combine like terms: -9.2 + -12.3 = -21.5 2x = -21.5 Divide each side by '2'. x = -10.75 Simplifying x = -10.75
| 10x-15=9x+10 | | 59-3x=5-9x | | x+10=-47 | | x+2+1=9 | | 7x-5=5x+27 | | 6c-86=3c-14 | | 3x+18=6x-9 | | 6x+6=-38-5x | | 3ab+7b= | | 7+6x=-18+x | | 6x^2+6y^2=144 | | 7+6x=-18x+x | | 13-3x=5-2x | | -4x+14=54 | | 9h+10h+7h-6h-16h=10 | | 6(x+2)=6x+14 | | 4(x+6)+3=-3 | | 11r^2-15r=-4 | | 5+65c=39c+13 | | 17j-16j-j+j=16 | | 6k-4k-k=12 | | 6k+5k+16k+4k=15 | | 6c+c+2c=9 | | -8+2c=-32+11c | | 26=3b-2-1b | | cosx=10x | | 2c-5c=14 | | 10g-5g+4g-2g-2g=20 | | 2x(3x+5)+5=8 | | 4c+9=-57-7c | | 20m+5m-21m-2m=14 | | 3(x+4)-7=29 |